Clean and efficient process for the extraction of rubidium from granitic rubidium ore. (20th September 2018) - Xing, Peng; Wang, Chengyan; Wang, Ling; Ma, Baozhong; Chen, Yongqiang; Wang, Guodong
Abstract: The extraction of rubidium from natural resources has attracted much attention due to its growing application in many fields. This paper presents a novel clean process for extracting rubidium from granitic rubidium ore. The process consists of alkaline leaching, desilication, and solvent extraction. The experiment results show that the leaching ratio of Rb can be greater than 95% at a leaching temperature of 230 °C, NaOH concentration of 200 g/L, particle size of 100 mesh, liquid/solid ratio of 10:1, leaching time of 1 h, and stirring rate of 500 rpm. The optimum conditions for the desilication were determined to be the temperature of 95 °C, mass ratio of CaO to SiO2 of 1.2, and reaction time of 1 h. The SiO2 precipitation under optimum conditions was up to 96.2%. Approximately 98% of Rb in desilication liquor was extracted using 1 mol/L 4- tert -butyl-2-( α -methylbenzyl) phenol (in xylene) in three stages at a phase ratio (O/A) of 3:1 for 1.5 min and more than 99% of Rb in loaded organic phase was stripped using 1 mol/L HCl in two stages at a phase ratio of 10:1. The raffinate of Rb can be sent to the leaching step again after the extraction of potassium to close the loop. The results of mineralogy research suggest that the rubidium-bearing micas and feldspar were altered to zeolite and cancrinite during the hydrothermal alkaline leaching, which contributed to the release of rubidium from ore. Compared with the existing processes, this process has the advantages of lower energy consumption and no wastewater/emission gas disposals. In addition, the solid wastes can be utilized as the value-added products. Highlights: The novel process is simple, eco-efficient, and environmentally friendly. 95.1% of rubidium was leached from ore by hydrothermal alkaline leaching. 96.2% of the silica in leaching liquor was precipitated with calcium oxide. Rubidium in desilication liquor was completely extracted by solvent extraction. Micas and feldspar were altered to zeolite and cancrinite in alkaline leaching.